EFEKTIVITAS MEDIASI DALAM MENGURANGI ANGKA PERCERAIAN (STUDI KASUS DI PENGADILAN AGAMA KABUPATEN MALANG KELAS IA) - Putri Malikha; Ibn Jazari; Syamsu Madyan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Marriage is proof of the seriousness of a man's love for a woman to be his life partner. In the world of marriage it is impossible to run smoothly, more or less there must be problems in it. But it depends on each partner in responding. Constant quarrels in the household can lead to divorce. When a couple has filed for divorce to a religious court, later there must be something called mediation. The Religious Courts as the implementing body of judicial power, of course have the authority to receive, examine, and decide a case. The judge as the executor of justice must seek peace to the litigants. The peace effort is called mediation, which is carried out by the mediator. The mediator is a neutral party who assists the litigating parties in the negotiation process in order to resolve disputes without resorting to breaking or imposing a settlement. This study will discuss the benefits of mediation, the effectiveness of mediation in reducing divorce rates and the role of mediators in the divorce process. Mediation itself aims to reconcile or reconcile the litigants, especially when they can reconcile and return to influence the ark of a sakinah mawaddah wa rahmah household